Dynamics of sun‐induced chlorophyll fluorescence and reflectance to detect stress‐induced variations in canopy photosynthesis. (3rd May 2020) - Pinto, Francisco; Celesti, Marco; Acebron, Kelvin; Alberti, Giorgio; Cogliati, Sergio; Colombo, Roberto; Juszczak, Radosław; Matsubara, Shizue; Miglietta, Franco; Palombo, Angelo; Panigada, Cinzia; Pignatti, Stefano; et al.
Abstract: Passive measurement of sun‐induced chlorophyll fluorescence ( F ) represents the most promising tool to quantify changes in photosynthetic functioning on a large scale. However, the complex relationship between this signal and other photosynthesis‐related processes restricts its interpretation under stress conditions. To address this issue, we conducted a field campaign by combining daily airborne and ground‐based measurements of F (normalized to photosynthetically active radiation), reflectance and surface temperature and related the observed changes to stress‐induced variations in photosynthesis. A lawn carpet was sprayed with different doses of the herbicide Dicuran. Canopy‐level measurements of gross primary productivity indicated dosage‐dependent inhibition of photosynthesis by the herbicide. Dosage‐dependent changes in normalized F were also detected. After spraying, we first observed a rapid increase in normalized F and in the Photochemical Reflectance Index, possibly due to the blockage of electron transport by Dicuran and the resultant impairment of xanthophyll‐mediated non‐photochemical quenching. This initial increase was followed by a gradual decrease in both signals, which coincided with a decline in pigment‐related reflectance indices. In parallel, we also detected a canopy temperature increase after the treatment. These results demonstrate the potential of using F coupled with relevant reflectance indices to estimate stress‐induced changes in canopy photosynthesis. Abstract : Passive measurement of sun‐induced chlorophyll fluorescence is a promising tool to quantify stress‐induced changes in photosynthetic functioning on a large scale. In this study, aerial measurements of fluorescence clearly tracked functional impairment of the rate of photosynthetic electron transport and carbon assimilation induced by a treatment with the herbicide Dicuran. Ancillary remote sensing variables such as vegetation indices and canopy temperature were used to quantify the dynamics of non‐photochemical energy dissipation mechanisms, the amount and composition of photosynthetic pigments and the stomatal activity. These results demonstrate the potential of using sun‐induced chlorophyll fluorescence coupled with relevant reflectance indices to estimate stress‐induced changes in canopy photosynthesis.